2016
DOI: 10.1111/nbu.12243
|View full text |Cite
|
Sign up to set email alerts
|

Is the British diet improving?

Abstract: The UK government's National Diet and Nutrition Survey report of Years 5 and 6 (2012/2013–2013/2014) of the Rolling Programme has just been published. By and large, the results are not encouraging. Compared to previous results from 2008/2009, little has changed and the national sample of children and adults continues to report eating too much saturated fat, non‐milk extrinsic sugars, too few fruit and vegetables and not enough oil‐rich fish, with certain groups of the population found to have low levels of som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“… 63 Another important trend is that Japan and France seem to have largely resisted a degradation of their diets, 64 , 65 but not the US 66 and England and Wales. 67 There is not enough literature to determine the extent to which food consumption has changed in Norway and Sweden.…”
Section: Discussionmentioning
confidence: 99%
“… 63 Another important trend is that Japan and France seem to have largely resisted a degradation of their diets, 64 , 65 but not the US 66 and England and Wales. 67 There is not enough literature to determine the extent to which food consumption has changed in Norway and Sweden.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, consumers' health, and ethical issues such as animal welfare, are feeding the controversy associated with meat consumption. However, not all consumers in Western countries are willing to reduce their meat consumption [2][3][4][5].…”
Section: Introduction 1the Background To the Rise In Meat Substitutesmentioning
confidence: 99%
“…61 Although there doesn’t appear to be country-specific data for the other nations we examine, one study found that in high-income Western countries, between 2001 and 2016, physical inactivity increased by 5%. 62 Another important trend is that Japan and France seem to have largely resisted “Westernization”/degradation of their diets, 63,64 but not the US 65 and England and Wales 66 . There is not enough literature on the diets in Norway and Sweden to determine the extent to which their diets have changed.…”
Section: Discussionmentioning
confidence: 99%